Multiplexed structured illumination super-resolution imaging with lifetime-engineered upconversion nanoparticles - Liu, Baolei; Liao, Jiayan; Song, Yiliao; Chen, Chaohao; Ding, Lei; Lu, Jie; Zhou, Jiajia; Wang, Fan (Nanoscale advances, 2021)
The emerging optical multiplexing within nanoscale shows super-capacity in encoding information by using lifetime fingerprints from luminescent nanoparticles. However, the optical diffraction limit compromises the decoding accuracy and throughput of the nanoparticles during conventional widefield imaging. This, in turn, challenges the quality of nanoparticles to afford the modulated excitation condition and further retain the multiplexed optical fingerprints for super-resolution multiplexing. Here we report a tailor-made multiplexed super-resolution imaging method using the lifetime-engineered upconversion nanoparticles. We demonstrate that the nanoparticles are bright, uniform, and stable under structured illumination, which supports a lateral resolution of 185 nm, less than 1/4th of the excitation wavelength. We further develop a deep learning algorithm to coordinate with super-resolution images for more accurate decoding compared to a numeric algorithm. We demonstrate a three-channel super-resolution imaging based optical multiplexing with decoding accuracies above 93% for each channel and larger than 60% accuracy for potential seven-channel multiplexing. The improved resolution provides high throughput by resolving the particles within the diffraction-limited spots, which enables higher multiplexing capacity in space. This lifetime multiplexing super-resolution method opens a new horizon for handling the growing amount of information content, disease source, and security risk in modern society. We report a tailor-made multiplexed super-resolution imaging method using the lifetime fingerprints from luminescent nanoparticles, which can resolve the particles within the diffraction-limited spots and enable higher multiplexing capacity in space.